North American tunneling 2006 [electronic resource] : proceedings of the North American tunneling conference 2006 ;10-15 June 2006, Chicago, USA - Proceedings of the North American Tunneling 2006 Conference (2006 : Chicago, USA); Ozdemir, Levent (Netherlands : Taylor & Francis, 2006)
PSZJBL